Asymmetric Formal Synthesis of (–)-Swainsonine from Chiral-Pool Precursors d-Mannose and d-Arabinose - Lamor, Anphisa; Uipanit, Suwanan; Yakhampom, Sujitra; Ngernmeesri, Paiboon; Kongkathip, Ngampong; Kongkathip, Boonsong; Chuanopparat, Nutthawat (Synlett, 2022)
Carbohydrates have played an important role in organic synthesis. Since they contain many stereocenters, they have been widely used as chiral-pool starting materials. Herein, we report the asymmetric formal synthesis of (–)-swainsonine, which exhibits anticancer and immunosuppressive activities and inhibits lysosomal α-mannosidase activity, from d-mannose and d-arabinose. The synthesis utilized Zn-mediated Bernet–Vasella reaction, Horner–Wadsworth–Emmons olefination, and Grubbs olefin metathesis as key reactions.
Keywords: arabinose; mannose; swainsonine; natural product synthesis; anticancer